A review of genus-group names in Diptera (Insecta) that J.C. Fabricius “borrowed” from other dipterists and proposed as new in his systematic works from 1775 to 1805 - Michelsen, Verner; O’hara, James E. (Zootaxa, 2014)
It is shown that a total of eight pre-existing genus-group names in Diptera were “borrowed” and deliberately given new identities in the systematic works of J.C. Fabricius: Bibio Fabricius, 1775, Ceria Fabricius, 1794, Hirtea Fabricius, 1798, Mulio Fabricius, 1798, Scatophaga Fabricius, 1805, Sicus Fabricius, 1798, Thereva Fabricius, 1798 and Voluccella Fabricius, 1794. These names are reviewed from the standpoint that they are nomenclaturally available as intentional homonymous proposals of names for new genus-group taxa. New type-species designations are made for Bibio Fabricius, Mulio Fabricius, and Scatophaga Fabricius. Bibio Fabricius, 1775 is recognized as a senior synonym of Thereva Latreille, 1797, syn. n., but is invalid as it is a junior homonym of Bibio Geoffroy, 1762. Scatophaga Fabricius, 1805 is recognized as a junior synonym of Psila Meigen, 1803, syn. n. The nominal species Musca suilla Fabricius, 1794 has been misinterpreted as a species of Scathophaga Meigen, 1803 by subsequent authors. Scathophaga spurca Meigen, 1826 is revived as the valid name for Scathophaga suilla auct. nec (Fabricius, 1794), stat. rev. A lectotype is designated for Musca suilla Fabricius and it is shown to belong to the scathophagid Norellisoma spinimanum (Fallén, 1819), syn. n. In order to maintain stability of nomenclature and prevailing usage, reversal of precedence is invoked to declare Cordylura spinimana Fallén, 1819 as a nomen protectum and Musca suilla Fabricius, 1794 as a nomen oblitum.